DIGITAL MARKETING - Khusanboyeva Tursunoy Mukhammadkasimdzhanovna (Ecominds Press, 2025)
This article covers the main types, advantages, strategies of digital marketing and their impact on business. In particular, areas such as content marketing, social media marketing, SEO (search engine optimization), email marketing and digital advertising are widely discussed. At the same time, methods for effective use of digital marketing tools, identification of target audience and measurement of advertising effectiveness are also described. The results of the study show that digital marketing is one of the fastest growing and effective marketing tools today, which also creates wide opportunities for small and medium-sized businesses.